Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1439-0507.2009.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence ability of Candida africana: a comparative study with Candida albicans and Candida dubliniensis

Abstract: In this study, we compared the adherence ability to human Hela cells and biofilm formation of three closely related Candida yeast. In our experiments, Candida africana showed poor adhesion ability to human Hela cells and the absence of biofilm formation on polyvinyl chloride strips. Conversely, Candida albicans and Candida dubliniensis formed mature biofilms and stable attachment to Hela cells. To our knowledge, this is the first comparative study reporting data on biofilm formation and adherence to human Hela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…africana among HIV‐infected patients in Cameroon. The isolation of the yeast in vaginal fluid is in accordance with what has been found previously, supporting the vaginal mucosa as a particular niche for C. africana . The patients’ CD4+ counts were higher enough to not consider the immunosuppression as being involved in the presence of the yeast.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…africana among HIV‐infected patients in Cameroon. The isolation of the yeast in vaginal fluid is in accordance with what has been found previously, supporting the vaginal mucosa as a particular niche for C. africana . The patients’ CD4+ counts were higher enough to not consider the immunosuppression as being involved in the presence of the yeast.…”
Section: Discussionsupporting
confidence: 89%
“…The patients’ CD4+ counts were higher enough to not consider the immunosuppression as being involved in the presence of the yeast. In fact, it has already been shown that C. africana might colonise mucosae without a real implication in an infection . The patient with itching also presented Gardnerella vaginalis , a bacterium that colonises vaginal mucosa, thereby destroying Lactobacillus , providing a free space for the development of opportunistic pathogens such as Candida species .…”
Section: Discussionmentioning
confidence: 99%
“…The hwp1 gene in C. albicans is reported to be an important adhesin that crosslinks C. albicans to epithelial cells. The distinct hwp1 allele found in C. africana may be responsible for the low hyphal production, reduced adhesion and decreased virulence . Similarly, the rlm1 gene is required for cell wall integrity under stressed conditions such as the presence of the antifungal caspofungin.…”
Section: Discussionmentioning
confidence: 99%
“…This amino sugar is metabolized by all typical C. albicans strains investigated (Tietz et al, 1995) and it is essential for various cellular processes in this species including white-opaque switching and yeast-to-hyphal transition (Huang et al, 2010; Konopka, 2012). In addition, C. africana also shows poor adhesion to human epithelial cells (Romeo et al, 2011), a notable low level of filamentation (Borman et al, 2013) and decreased virulence as recently demonstrated using both mammalian and insect infection models (Borman et al, 2013; Pagniez et al, 2015). All these characteristics could be the reflection of a peculiar genetic background that is worth to be investigated in detail.…”
Section: Introductionmentioning
confidence: 92%